Determinant Factors of People’s Business Credit (KUR) Repayment in The Livestock Sector - Syahfrizal, Aldi; Muzayyanah, Mujtahidah Anggriani Ummul; Wankar, Tian Jihadhan (Buletin Peternakan, 2025)
The People's Business Credit (KUR) program plays a crucial role in supporting Indonesia's livestock sector, which remains a primary source of livelihood for many rural households. This study aims to identify the characteristics of livestock farmers receiving KUR and the factors influencing loan repayment. Data were collected through a survey of 505 livestock farmers in Purbalingga Regency who had received KUR financing. A binary logistic regression model was used to analyze the determinants of loan repayment. The results show that borrower age, loan amount, loan term, and credit risk score significantly affect loan repayment performance. In contrast, gender, number of dependents, education level, business experience, income, and repayment capacity do not have a significant effect. The findings suggest that borrower characteristics and loan terms are crucial in determining repayment outcomes. Policymakers are advised to align KUR loan terms with livestock production cycles and provide financial literacy support to improve repayment rates and ensure the long-term sustainability of livestock-based KUR programs.